Hubungan Pengetahuan Dan Pendapatan Kepala Keluarga Dengan Kepemilikan Jamban Sehat - Ni Made Rina Febriyanti; Ni Ketut Rusminingsih; I Nyoman Purna (Poltekkes Kemenkes Denpasar, 2021)
Abstract: The people in Dauh Puri Kaja Village still do a lot of defecation in the river, this is because people who behave in defecating do not have healthy latrines in their households. Researchers want to know the relationship between knowledge and income of household heads with ownership of healthy latrines. This type of research uses an analytic survey with an interview method with a case control approach. The sample of the study was 72 households consisting of 36 families who did not have healthy latrines as the case group and 36 families who had healthy latrines as the control group. The sampling technique was purposive sampling. Data were collected using a questionnaire sheet, statistical analysis using the Chi Square test. The results of the level of knowledge of the head of the household regarding healthy latrines were 38 respondents (52.8%) with a poor level of knowledge. The results of the income level of the head of the family, namely having a low income level, were 41 respondents (56.9%).The results of the Chi Squares test show that there is a relationship between knowledge and ownership of healthy latrines (ρ value = 0,000 0,05) and the level of a strong relationship (CC = 0,615). And there is a relationship between the income of the head of the household and ownership of a healthy latrine (ρ value = 0.000 0,05) and the level of relationship is moderate (CC = 0,574). It is recommended that the community increase their knowledge of healthy latrines.